Kualitas Daya pada Microgrid Gangguan, Standar, dan Studi Kasus - Mohamad Isnaeni Romadhon (Knowledge on Sustainability, Longevity, and Interdisciplinary, 2025)
The global growth of renewable energy-based power generation has accelerated significantly in recent years. This transformation requires modernized electric grids that incorporate digital technologies, distributed generation (DG), and the integration of renewable energy sources (RES). Microgrid (MG) technology has emerged as a promising solution to enable the effective integration of DG and facilitate the deployment of RES connected to the grid. However, the increasing complexity of MG systems brings new challenges, particularly in ensuring power quality (PQ) that complies with established grid standards. This article provides an overview of PQ issues in MGs, including various types of disturbances, their main characteristics, and relevant PQ standards. In addition, a case study on PQ analysis in a published MG system is presented. Overall, the article highlights the importance of maintaining PQ in microgrids to ensure reliable and stable operation in future energy systems.